2015
DOI: 10.1002/smll.201502730
|View full text |Cite
|
Sign up to set email alerts
|

Dose‐Dependent Therapeutic Distinction between Active and Passive Targeting Revealed Using Transferrin‐Coated PGMA Nanoparticles

Abstract: The paradigm of using nanoparticle-based formulations for drug delivery relies on their enhanced passive accumulation in the tumor interstitium. Nanoparticles with active targeting capabilities attempt to further enhance specific delivery of drugs to the tumors via interaction with overexpressed cellular receptors. Consequently, it is widely accepted that drug delivery using actively targeted nanoparticles maximizes the therapeutic benefit and minimizes the off-target effects. However, the process of nanoparti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 43 publications
0
32
0
Order By: Relevance
“…Targeting TfR1 using drugs and drug delivery systems functionalized with transferrin, antibodies, antibody-derivatives, or TfR-targeted peptides, is a commonly employed and arguably the best-known strategy, as illustrated by its usage as a prototypical system for mechanistic studies of active targeting to cancer cells228. An impressive amount of different TfR-targeted delivery systems have been designed and evaluated for cancer therapy by exploiting the increased expression of TfR in some tumours, and this strategy has shown preclinical benefit when using a low-dose regimen229. At least three TfR-targeted systems are currently under clinical development (Table 3)(MBP-426, Mebiopharm; SGT-53, SGT-94, SynerGene Therapeutics)230,231.…”
Section: Iron Metabolism As a Therapeutic Targetmentioning
confidence: 99%
“…Targeting TfR1 using drugs and drug delivery systems functionalized with transferrin, antibodies, antibody-derivatives, or TfR-targeted peptides, is a commonly employed and arguably the best-known strategy, as illustrated by its usage as a prototypical system for mechanistic studies of active targeting to cancer cells228. An impressive amount of different TfR-targeted delivery systems have been designed and evaluated for cancer therapy by exploiting the increased expression of TfR in some tumours, and this strategy has shown preclinical benefit when using a low-dose regimen229. At least three TfR-targeted systems are currently under clinical development (Table 3)(MBP-426, Mebiopharm; SGT-53, SGT-94, SynerGene Therapeutics)230,231.…”
Section: Iron Metabolism As a Therapeutic Targetmentioning
confidence: 99%
“…4,1113 Transferrin adsorbed by the polystyrene and poly(glycidyl methacrylate) ENMs could actively target the breast or prostate cancer cells overexpressing transferrin receptor. 8,14,15 However, serum albumin could reduce the targeting capability of such ENMs if co-existing in the surrounding environment, 16 probably because albumin displaces transferrin off the ENM surface or interferes with receptor binding by covering up the binding sites on transferrin. Besides the type and affinity of the adsorbed proteins, changes to protein conformation upon adsorption could alter the biological responses to ENMs.…”
mentioning
confidence: 99%
“…In contrast to free DTX that showed low cytotoxicity at a high DTX concentration, improved cytotoxicity of Tf‐modified DTX nanomedicine was observed as a result of the targeting effect and enhanced stability in cell medium . As aforementioned, drug delivery mediated by positive targeting initially relies on the passive targeting, which suggests that the positive and passive drug delivery mechanisms are interrelated. Adopting Tf as the positive targeting group ( Figure ), Singh et al found both the passive targeting and positive targeting exhibited dose‐dependent therapeutic distinction .…”
Section: Positive Targetingmentioning
confidence: 95%
“…Positive targeting (i.e., active targeting) serving as a complementary paradigm for passive targeting has been widely established for tumor chemotherapy. Generally, positive targeting initially depends on the passive accumulation of nanomedicines in tumors . Positive targeting relies on the presence of certain tumor biomarkers or unique tumor microenvironment.…”
Section: Positive Targetingmentioning
confidence: 99%